Incidence and severity of postoperative pain following root canal treatment in nonvital pulps with hand and rotary instrumentation techniques in Chhattisgarh Population - Mahesh Motlani; P Krishna Prasad; Ramanpal Singh Makkad; Rashmi Nair; Saara Khiyani; Sushmita Batra (Wolters Kluwer Medknow Publications, 2021)
Aim: To evaluate the incidence and severity of postoperative pain following root canal treatment in nonvital pulps with hand and rotary instrumentation techniques in Chhattisgarh population. Materials and Methods: Sixty asymptomatic single-canaled nonvital teeth were selected and were divided into two groups of 30 each. Group I: 30 single-canalled teeth were treated in a single visit and prepared with hand file system. Group II: 30 single-canaled teeth treated in a single visit and prepared with K3-rotary file system. Group I and II were divided into two subgroups of 15 each (Group IA, IB and Group IIA, IIB) which were irrigated with 2% chlorhexidine and 5.25% sodium hypochlorite, respectively. The patients were recalled at 24, 48, and 72 h and at 1 week to record the incidence and severity of postoperative pain by using visual analog scale. Results: Results showed low incidence and severity of postoperative pain following a single-visit treatment with rotary instrumentation when compared to hand instrumentation technique. No statistical significant difference was observed between the groups at different time intervals, i.e., at 24, 48, and 72 h and at 1 week. The use of recent endodontic techniques and devices reduces the postoperative pain. Conclusions: Postoperative pain after root canal treatment ranged from mild to severe and it can happen even after high-standard root canal treatment. There is low incidence and severity of postoperative pain following a single-visit treatment with rotary instrumentation when compared to hand instrumentation technique.